REALITAS ASPEK EKONOMI-SOSIAL MASYARAKAT KUBU DALAM METAFOR BAHASA SUKU KUBU DI JAMBI (The Reality of Social-Economic Aspects of Kubu Society in The Metaphor of Kubu Language in Jambi) - Natal P. Sitanggang (Balai Bahasa Sulawesi Selatan, 2014)
This article discusses a certain Kubu culture in Bukit Duabelas, Jambi Province based on lingustic perspective, metaphor. Linguistically, metaphor is explained by the formation of its concept and contexts. The fact of the metaphor is gained from the daily conversation of Kubu tribe and analyzed pragmatically and interpretatively to compare and to relate metaphor signs with the intended meaning. In this study, it is found that there is a relevance between social-economy and the form of the metaphor used. Diachronically, it is also found that there is a relationship between the metaphor of Malay/Indonesian and the metaphor of Kubu language. That is why, this study becomes an important reference in tracing a part of prototype and metaphoric contextual analogyfound in Malay/ Indonesian. This is believed because some Malay culture can still be seen in primitive life of Kubu tribe at the moment.